Pseudocapacitance supercapacitor electrode material, hydrogenated TiO2 nanotube and preparation method

By using the metal-acid surface hydrogenation method to prepare TiO2 nanotube array electrodes at room temperature and normal pressure, the experimental conditions and safety hazards of preparing positive electrode materials under high temperature and nitrogen atmosphere in the prior art were solved, and the preparation of the positive electrode materials with high energy density and high power density was realized.

CN119601391APending Publication Date: 2025-03-11ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411164273.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art needs to be carried out in a high-energy and high-power density pseudocapacitor supercapacitor positive electrode material with high energy density and high power density. The experimental conditions are harsh, the cost is high, the process is complex and there are safety hazards.

Method used

The metal-acid surface hydrogenation method at room temperature and normal pressure was used to prepare the TiO2 nanotube array electrode by anodizing method, and the surface hydrogenation was carried out under room temperature to improve the conductivity, thereby preparing the H-TiO2NTs@MnO2 positive electrode material with high energy density and high power density.

Benefits of technology

It significantly improves the conductivity and electrochemical performance of the electrode material, improves the energy density and power density of the supercapacitor, reduces the preparation cost, simplifies the process, and avoids safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601391A_ABST
    Figure CN119601391A_ABST
Patent Text Reader

Abstract

The invention discloses a pseudocapacitance supercapacitor electrode material, a hydrogenated TiO2 nanotube and a preparation method, and belongs to the technical field of supercapacitor electrode material preparation. The invention relates to a method for preparing a hydrogen-doped titanium dioxide nanotube array (H-TiO2NTs) by using a surface hydrogenation method at normal temperature and normal pressure, and the hydrogen-doped titanium dioxide nanotube array (H-TiO2NTs) is used for loading MnO2 so as to improve the energy density and the power density of a super capacitor positive electrode material and a water-phase asymmetric super capacitor. The H-TiO2NTs is successfully prepared by taking dilute sulphuric acid, Zn and TiO2NTs as raw materials under the conditions of normal temperature and oxygen production for the first time, and the H-TiO2NTs is used as a matrix to load MnO2 through electro-deposition. The conductivity of the H-TiO2NTs is increased, so that the electrochemical energy storage performance of the composite electrode material is excellent. Compared with a traditional hydrogen atmosphere and high-temperature calcination hydrogen doping method, the method is simple in experimental condition, efficient, economical and environmentally friendly, and has a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of high-performance pseudocapacitor supercapacitor electrode materials, and specifically to the preparation of hydrogenated TiO2 nanotubes at room temperature and pressure, and a method for preparing H-TiO2NTs@MnO2, a positive electrode material for pseudocapacitors with high energy density and high power density, by using the hydrogenated TiO2 nanotubes to load MnO2. Background Art

[0002] MnO2 is considered an ideal cathode material in aqueous asymmetric supercapacitors due to its high reversibility of redox reactions, fast electron transfer speed, high specific capacity of 1400F / g, and environmental friendliness. However, during capacitor assembly, only MnO2 in contact with water can store / release charges well, while the unexposed active sites contribute little to charge storage. For this reason, MnO2 is often loaded onto a matrix material with a large specific surface area to improve the utilization of MnO2 electrode materials.

[0003] TiO2 nanotubes are highly ordered, vertically oriented, and have a large surface area, making them good carriers. However, their low electrical conductivity limits the power density and energy density of composite electrode materials. The common high-temperature / H2 atmosphere hydrogen doping method can significantly improve the electrical conductivity of TiO2, but because it needs to be performed at above 600°C and in a hydrogen atmosphere, the experimental conditions are demanding, the cost is high, the process is complex, and there are serious safety hazards, which limits the application of this method.

[0004] After searching, the patent number is ZL201310475458.8, and the patent name is: A high energy density and long life manganese oxide / titanium oxynitride supercapacitor material and its preparation; the preparation steps of this application are: (1) Prepare titanium dioxide nanotubes by anodic oxidation: a titanium metal foil with a thickness of 50±10 microns and a purity of 99.8% is used as the anode, one side of which is in contact with the ethylene glycol electrolyte, and the cathode is also made of titanium metal foil; the electrolyte is kept constant at 20±5℃, and the voltage between the anode and the cathode is kept at 50±8V. After anodic oxidation, a TiO2 nanotube array is obtained; (2) the TiO2 nanotube array is subjected to a heat nitridation treatment at 600℃-900℃ in an ammonia atmosphere in a tube furnace for 35±15 minutes to obtain titanium oxynitride TiO 1-x N x Nanotube array, 0.6≥x>0; (3) In the above TiO 1-x N x A manganese dioxide nanolayer is deposited on the surface of the nanotube array to obtain a flexible supercapacitor material. The application also requires that it be carried out at high temperature and in a nitrogen atmosphere, which still has the problem of relatively harsh experimental conditions. Summary of the invention

[0005] 1. Technical problem to be solved by the invention

[0006] The purpose of the present invention is to apply the metal-acid surface hydrogenation method at room temperature and pressure in the field of photothermal-biology to the preparation of supercapacitor composite positive electrode materials for the first time. The present invention prepares TiO2 nanotube array electrodes by anodization, and realizes surface hydrogenation at room temperature and pressure, thereby improving the conductivity of the electrode material, thereby comprehensively improving the energy density and power density of the electrode material and the water-based asymmetric supercapacitor.

[0007] 2. Technical solution

[0008] In order to achieve the above object, the technical solution provided by the present invention is:

[0009] A method for preparing hydrogenated TiO2 nanotubes of the present invention comprises the following steps:

[0010] (1) After the titanium sheet is polished to a smooth surface, it is ultrasonically cleaned in acetone, ethanol, and distilled water in sequence, then rinsed with deionized water and dried for later use;

[0011] (2) mixing ammonium fluoride, deionized water and ethylene glycol and stirring them evenly to form an electrolyte;

[0012] (3) using the titanium sheet processed in step (1) as an anode and the graphite sheet as a cathode, and performing an anodic oxidation treatment on the titanium sheet in the electrolyte prepared in step (2);

[0013] (4) The titanium sheet after anodization in step (3) is repeatedly washed with deionized water and ethanol, placed in a constant temperature drying oven for drying, and then calcined in an air atmosphere and kept warm for a period of time, and taken out after cooling to room temperature to obtain a TiO2NTs electrode;

[0014] (5) preparing a dilute sulfuric acid solution, placing the TiO2NTs electrode prepared in step (4) in the prepared solution, placing a zinc sheet on the surface of the TiO2NTs electrode, and washing with deionized water after the reaction is completed and drying in an oven to obtain an H-TiO2NTs electrode, i.e., hydrogenated TiO2 nanotubes.

[0015] Furthermore, in step (2), the content of ammonium fluoride is 0.2 wt.% to 0.5 wt.%, and the content of deionized water is 1 vol.% to 5 vol.%.

[0016] Furthermore, in step (3), the titanium sheet is anodized in an electrolyte at a reaction temperature of 20 to 25° C., a voltage of 30 to 80 V, and an anodization time of 1 to 6 hours.

[0017] Furthermore, in step (4), the anodized titanium sheet is repeatedly cleaned with deionized water and ethanol, placed in a constant temperature drying oven for drying, and then placed in a muffle furnace, and the temperature is increased to 550° C. at a rate of 5 to 10° C. / min, and kept warm for two hours.

[0018] Furthermore, in step (5), a 1-10 vol.% dilute sulfuric acid solution is prepared, and the area of ​​the zinc sheet is 1-10 mm 2 , purity is 99.99%, place the zinc sheet on the TiO2NTs electrode surface for 10 to 30 minutes, and keep the solution temperature between 20 and 50°C for reaction; after the reaction, wash with deionized water and dry in an oven at 40 to 100°C.

[0019] The hydrogenated TiO2 nanotube of the present invention is prepared by the above method.

[0020] The invention discloses a method for preparing a pseudocapacitor supercapacitor electrode material. The prepared hydrogenated TiO2 nanotubes are used as working electrodes, platinum sheets are used as counter electrodes, Ag / AgCl electrodes are used as reference electrodes, and a mixture of Na2SO4 and MnSO4 is used as an electrolyte. Constant potential electrodeposition is performed to prepare the pseudocapacitor supercapacitor electrode material H-TiO2NTs@MnO2.

[0021] Furthermore, the electrolyte contains SO4 2- The concentration is 0.5~1.0mol / L.

[0022] Furthermore, during constant potential electrodeposition, the electrolyte temperature is 20-50° C., the electrodeposition voltage is 0.8-1.2 V, and the deposition time is 5-10 min.

[0023] The pseudocapacitor supercapacitor electrode material of the present invention is prepared by the above method.

[0024] 3. Beneficial effects

[0025] Compared with the existing known technologies, the technical solution provided by the present invention has the following significant effects:

[0026] (1) The present invention uses titanium sheet as the substrate, prepares TiO2NTs electrode by anodic oxidation, and realizes surface hydrogenation of TiO2NTs by zinc-sulfuric acid method at room temperature and atmospheric pressure. In terms of electrochemical performance, the TiO2NTs electrode has a discharge current of 100 μA cm -2 The surface capacitance is only 0.1-0.2 mF cm -2 The surface capacitance of H-TiO2NTs reached 4.4-11.8mF cm -2The surface capacitance increased by more than 60 times, showing excellent cycle stability with a current density of 100 mA cm -2 After 5000 cycles under the same conditions, it remains above 87%.

[0027] (2) The H-TiO2NTs electrode prepared by the present invention through surface modification has a Fermi level difference. The metal with a lower work function provides electrons to the TiO2NTs interface, attracts surrounding protons to penetrate into the TiO2NTs in the acidic solution, improves the microstructure of the material, and enhances the electrical conductivity.

[0028] (3) The present invention first improves the conductivity of TiO2 by doping with hydrogen rather than nitrogen; secondly, the hydrogen doping method is carried out at room temperature and pressure, and the cost is one percent of that of calcination at high temperature and H2 atmosphere, which has great potential for promotion and application; finally, the experimental conditions of the hydrogen doping method are mild and simple, which can avoid dangers such as explosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a top view SEM of the prepared H-TiO2NTs electrode material. The TiO2 nanotube array was treated by a hydrogen doping method at room temperature and pressure to obtain H-TiO2NTs. The diameter of the nanotubes is about 80nm.

[0030] Figure 2 This is a side view SEM of the prepared H-TiO2NTs electrode material. The TiO2 nanotube array was treated by a hydrogen doping method at room temperature and pressure to obtain H-TiO2NTs. The tube length of the H-TiO2NTs is about 20μm.

[0031] Figure 3 The XRD diagram of TiO2NTs material before and after H doping. Hydrogenation will reduce the XRD peak intensity of TiO2NTs. The XRD shift of TiO2 to a high angle may be caused by the introduction of defects, which will form more active sites and is beneficial to the improvement of capacitance performance.

[0032] Figure 4 The constant current charge and discharge (GCD) performance comparison chart of the prepared H-TiO2NTs is shown below: Figure 4 The curve is calculated as follows: At 100 μA cm -2 At a current density of 1.3 Å, the area specific capacity of TiO2NTs is 0.3 mF cm -2 The area specific capacities of H-TiO2NTs at anodization voltages of 50, 60, and 70 V are 4.4 mF cm -2 、7.0mF cm -2 、11.8mF cm -2The electrochemical performance is significantly improved after hydrogenation, with the highest area specific capacity being about 40 times that of the original titanium dioxide nanotubes.

[0033] Figure 5 This is the GCD performance diagram of the prepared H-TiO2NTs loaded MnO2 electrode material. At 300μA cm -2 At a current density of 1.3 %, the area specific capacity of H-TiO2NTs@MnO2 is 305 mF cm -2 ; at 3000μA cm -2 At a current density of 2.3 Å, the area specific capacity of H-TiO2NTs@MnO2 is 241 mF cm -2 When the current density increases tenfold, the area specific capacity only decreases by 21.0%. DETAILED DESCRIPTION

[0034] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings and embodiments.

[0035] Example 1

[0036] A hydrogenated TiO2 nanotube of this embodiment is prepared by the following method, the specific steps are:

[0037] (1) A titanium sheet with a purity of more than 99% was polished with sandpaper until the surface was smooth and flat, and then ultrasonically cleaned in acetone, ethanol, and distilled water for 15 min, then rinsed with deionized water, and dried for later use;

[0038] (2) stirring a mixed solution consisting of 0.3 wt.% ammonium fluoride, 2 vol.% deionized water and ethylene glycol to obtain an electrolyte;

[0039] (3) using the titanium sheet treated in step (1) as an anode and the graphite sheet as a cathode, and performing an anodizing treatment on the titanium sheet in the electrolyte prepared in step (2), wherein the reaction temperature is 20° C., the voltage is 50 V, and the anodizing time is 1.5 h;

[0040] (4) The titanium sheet after anodization in step (3) is repeatedly washed with deionized water and ethanol, placed in a constant temperature drying oven for drying, and then placed in a muffle furnace, and the temperature is raised to 550° C. at a rate of 10° C. / min, and kept at this temperature for two hours. After cooling to room temperature, the sheet is taken out to obtain a TiO2NTs electrode;

[0041] (5) Prepare a 10 vol% dilute sulfuric acid solution, place the TiO2NTs electrode prepared in step (4) in the prepared solution, and take a piece of 5 mm 2Zinc flakes with a purity of 99.99% were placed on the surface of the TiO2NTs electrode, the solution temperature was maintained at 30±10°C for 20 min, and then washed with deionized water and dried in an oven at 50°C to obtain H-TiO2NTs electrodes, i.e. hydrogenated TiO2 nanotubes.

[0042] Combination Figure 1-Figure 3 The morphology of the H-TiO2NTs electrode was characterized by SEM and XRD. It can be seen that the TiO2 nanotube array was treated by hydrogen doping method at room temperature and pressure to obtain H-TiO2NTs. The diameter of the nanotubes was about 80nm and the length was about 20μm. Hydrogenation would reduce the XRD peak intensity of TiO2NTs. Due to the generation of defects, the diffraction peak shifted to a high angle, and the introduction of defects increased the number of active sites, which was beneficial to the improvement of capacitance performance.

[0043] Supercapacitor performance test: H-TiO2NTs electrode is used as working electrode, graphite sheet is used as counter electrode, Ag / AgCl electrode is used as reference electrode, and 0.5M Na2SO4 is used as electrolyte. Test the GCD curve of H-TiO2NTs electrode material. Figure 4 , H-TiO2NTs at 100 μA cm -2 The area specific capacity at a current density of 4.4 mF cm -2 .

[0044] Example 2

[0045] A hydrogenated TiO2 nanotube of this embodiment is prepared by the following method, the specific steps are:

[0046] (1) A titanium sheet with a purity of more than 99% was polished with sandpaper until the surface was smooth and flat, and then ultrasonically cleaned in acetone, ethanol, and distilled water for 15 min, then rinsed with deionized water, and dried for later use;

[0047] (2) stirring a mixed solution consisting of 0.2 wt.% ammonium fluoride, 5 vol.% deionized water and ethylene glycol to obtain an electrolyte;

[0048] (3) using the titanium sheet treated in step (1) as an anode and the graphite sheet as a cathode, and performing an anodizing treatment on the titanium sheet in the electrolyte prepared in step (2), wherein the reaction temperature is 25° C., the voltage is 60 V, and the anodizing time is 1 h;

[0049] (4) The titanium sheet after anodization in step (3) is repeatedly washed with deionized water and ethanol, placed in a constant temperature drying oven for drying, and then placed in a muffle furnace, and the temperature is raised to 550° C. at a rate of 5° C. / min, and kept at this temperature for two hours. After cooling to room temperature, the titanium sheet is taken out to obtain a TiO2NTs electrode;

[0050] (5) Prepare 8 vol% dilute sulfuric acid solution, place the TiO2NTs electrode prepared in step (4) in the prepared solution, and take a piece of 10 mm 2 Zinc flakes with a purity of 99.99% were placed on the surface of the TiO2NTs electrode, the solution temperature was maintained at 40±10°C for 10 min, and then washed with deionized water and dried in an oven at 60°C to obtain H-TiO2NTs electrodes, i.e. hydrogenated TiO2 nanotubes.

[0051] Supercapacitor performance test: H-TiO2NTs electrode is used as working electrode, graphite sheet is used as counter electrode, Ag / AgCl electrode is used as reference electrode, and 0.5M Na2SO4 is used as electrolyte. Test the GCD curve of H-TiO2NTs electrode material. Figure 4 , H-TiO2NTs electrode at 100 μA cm -2 The area specific capacity at a current density of 7.0 mF cm -2 .

[0052] Example 3

[0053] A hydrogenated TiO2 nanotube of this embodiment is prepared by the following method, the specific steps are:

[0054] (1) A titanium sheet with a purity of more than 99% was polished with sandpaper until the surface was smooth and flat, and then ultrasonically cleaned in acetone, ethanol, and distilled water for 20 min, then rinsed with deionized water, and dried for later use;

[0055] (2) stirring a mixed solution consisting of 0.5 wt.% ammonium fluoride, 1 vol.% deionized water and ethylene glycol to obtain an electrolyte;

[0056] (3) using the titanium sheet treated in step (1) as an anode and the graphite sheet as a cathode, and performing an anodizing treatment on the titanium sheet in the electrolyte prepared in step (2), wherein the reaction temperature is 23° C., the voltage is 70 V, and the anodizing time is 4 h;

[0057] (4) The titanium sheet after anodization in step (3) is repeatedly washed with deionized water and ethanol, placed in a constant temperature drying oven for drying, and then placed in a muffle furnace, and the temperature is raised to 550° C. at a rate of 6° C. / min, and kept at this temperature for two hours. After cooling to room temperature, the titanium sheet is taken out to obtain a TiO2NTs electrode;

[0058] (5) Prepare a 2 vol% dilute sulfuric acid solution, place the TiO2NTs electrode prepared in step (4) in the prepared solution, and take a piece of 1 mm 2Zinc flakes with a purity of 99.99% were placed on the surface of the TiO2NTs electrode, the solution temperature was maintained at 30±5°C for 30 min, and then washed with deionized water and dried in an oven at 80°C to obtain H-TiO2NTs electrodes, i.e. hydrogenated TiO2 nanotubes.

[0059] Supercapacitor performance test: H-TiO2NTs electrode is used as working electrode, graphite sheet is used as counter electrode, Ag / AgCl electrode is used as reference electrode, and 0.5M Na2SO4 is used as electrolyte. Test the GCD curve of H-TiO2NTs electrode material. Figure 4 , H-TiO2NTs electrode at 100μAcm -2 The area specific capacity at the current density is 11.8 mF cm -2 .

[0060] Example 4

[0061] A pseudocapacitive supercapacitor electrode material H-TiO2NTs@MnO2 of this embodiment is prepared by the following method, specifically: using the prepared H-TiO2NTs as a working electrode, a platinum sheet as a counter electrode, Ag / AgCl (the electrolyte is saturated potassium chloride) as a reference electrode, and the electrolyte is a mixture of Na2SO4 and MnSO4, SO4 2- The concentration is 0.5 mol / L. During constant potential electrodeposition, the electrolyte temperature is 20°C, the electrodeposition voltage is 0.8 V, and the deposition time is 5 min.

[0062] Supercapacitor performance test: H-TiO2NTs@MnO2 electrode was used as the working electrode, graphite sheet as the counter electrode, Ag / AgCl electrode as the reference electrode, and 0.5M Na2SO4 as the electrolyte. Test the GCD curve of H-TiO2NTs@MnO2 electrode material. Figure 5 ,Depend on Figure 5 By integrating the curve, we can get H-TiO2NTs@MnO2 at 300μAcm -2 The area specific capacity at the current density is 305mF cm -2 , at 3000 μA cm -2 At a current density of 2.3 Å, the area specific capacity of H-TiO2NTs@MnO2 is 241 mF cm -2 When the current density increases tenfold, the area specific capacity only decreases by 21.0.

[0063] Example 5

[0064] A pseudocapacitive supercapacitor electrode material H-TiO2NTs@MnO2 of this embodiment is prepared by the following method, specifically: using the prepared H-TiO2NTs as a working electrode, a platinum sheet as a counter electrode, Ag / AgCl (the electrolyte is saturated potassium chloride) as a reference electrode, and the electrolyte is a mixture of Na2SO4 and MnSO4, SO4 2- The concentration is 0.8 mol / L. During constant potential electrodeposition, the electrolyte temperature is 30°C, the electrodeposition voltage is 0.9 V, and the deposition time is 8 min.

[0065] Example 6

[0066] A pseudocapacitive supercapacitor electrode material H-TiO2NTs@MnO2 of this embodiment is prepared by the following method, specifically: using the prepared H-TiO2NTs as a working electrode, a platinum sheet as a counter electrode, Ag / AgCl (the electrolyte is saturated potassium chloride) as a reference electrode, and the electrolyte is a mixture of Na2SO4 and MnSO4, SO4 2- The concentration is 1.0 mol / L. During constant potential electrodeposition, the electrolyte temperature is 50°C, the electrodeposition voltage is 1.2V, and the deposition time is 10min.

[0067] Comparative Example

[0068] The difference between this comparative example and Example 1 is that the prepared TiO2NTs electrode is not subjected to hydrogenation treatment.

[0069] Supercapacitor performance test: TiO2NTs electrode was used as working electrode, graphite sheet as counter electrode, Ag / AgCl electrode as reference electrode, and 0.5M Na2SO4 as electrolyte. The GCD curve of TiO2NTs electrode material was tested. The TiO2NTs electrode was tested at 100μA cm -2 The area specific capacity at the current density is 0.3mF cm -2 ,like Figure 4 shown.

[0070] The above work confirms that the H-TiO2NTs electrode prepared by surface modification, due to the Fermi level difference, the metal with a lower work function provides electrons to the TiO2NTs interface, attracts the surrounding protons to penetrate into the TiO2NTs in the acidic solution, improves the microstructure of the material, and enhances the conductivity.

[0071] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing hydrogenated TiO2 nanotubes, characterized in that: The following steps are involved: (1) After the titanium sheet is polished to a smooth surface, it is ultrasonically cleaned in acetone, ethanol, and distilled water in sequence, then rinsed with deionized water and dried for later use; (2) mixing ammonium fluoride, deionized water and ethylene glycol and stirring them evenly to form an electrolyte; (3) using the titanium sheet processed in step (1) as an anode and the graphite sheet as a cathode, and performing an anodic oxidation treatment on the titanium sheet in the electrolyte prepared in step (2); (4) The titanium sheet after anodization in step (3) is repeatedly washed with deionized water and ethanol, placed in a constant temperature drying oven for drying, and then calcined in an air atmosphere and kept warm for a period of time, and taken out after cooling to room temperature to obtain a TiO2NTs electrode; (5) preparing a dilute sulfuric acid solution, placing the TiO2NTs electrode prepared in step (4) in the prepared solution, placing a zinc sheet on the surface of the TiO2NTs electrode, and washing with deionized water after the reaction is completed and drying in an oven to obtain an H-TiO2NTs electrode, i.e., hydrogenated TiO2 nanotubes.

2. The method for preparing hydrogenated TiO2 nanotubes according to claim 1, characterized in that: In step (2), the content of ammonium fluoride is 0.2 wt.% to 0.5 wt.%, and the content of deionized water is 1 vol.% to 5 vol.%.

3. The method for preparing hydrogenated TiO2 nanotubes according to claim 2, characterized in that: Step (3) anodizes the titanium sheet in an electrolyte at a reaction temperature of 20 to 25° C., a voltage of 30 to 80 V, and anodizes for 1 to 6 hours.

4. The method for preparing hydrogenated TiO2 nanotubes according to claim 3, characterized in that: Step (4) The anodized titanium sheet is repeatedly cleaned with deionized water and ethanol, placed in a constant temperature drying oven to dry, and then placed in a muffle furnace, heated to 550° C. at a rate of 5 to 10° C. / min, and kept warm for two hours.

5. The method for preparing hydrogenated TiO2 nanotubes according to claim 4, characterized in that: Step (5) Prepare 1-10 vol.% dilute sulfuric acid solution, the area of ​​the zinc sheet is 1-10 mm 2 , purity is 99.99%, place the zinc sheet on the TiO2NTs electrode surface for 10 to 30 minutes, and keep the solution temperature between 20 and 50°C for reaction; after the reaction, wash with deionized water and dry in an oven at 40 to 100°C.

6. A hydrogenated TiO2 nanotube, characterized in that: Prepared by the method according to any one of claims 1 to 5.

7. A method for preparing a pseudocapacitor supercapacitor electrode material, characterized in that: The hydrogenated TiO2 nanotubes prepared by the method described in any one of claims 1 to 5 are used as working electrodes, platinum sheets are used as counter electrodes, Ag / AgCl electrodes are used as reference electrodes, and a mixture of Na2SO4 and MnSO4 is used as an electrolyte to perform constant potential electrodeposition to prepare pseudocapacitive supercapacitor electrode material H-TiO2NTs@MnO2.

8. The method for preparing a pseudocapacitive supercapacitor electrode material according to claim 7, characterized in that: The electrolyte contains SO4 2- The concentration is 0.5~1.0mol / L.

9. The method for preparing a pseudocapacitive supercapacitor electrode material according to claim 8, characterized in that: During constant potential electrodeposition, the electrolyte temperature is 20-50°C, the electrodeposition voltage is 0.8-1.2V, and the deposition time is 5-10min.

10. A pseudocapacitor supercapacitor electrode material, characterized in that: Prepared by the method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Preparation and silver doping methods of titania nanotubes

    CN103820834A

  • Nickel oxide / titanium oxide nanocomposite and preparation method and energy storage application therefor

    CN105448536A

  • Sunlight-driven electricity-oxygen co-production seawater battery and preparation method thereof

    CN112086289A

  • Preparing method of three-dimensional nickel / nickel-wire current collector deposited on NiCo2O4 nanostructure of flexible three-dimensional flower-like

    KR101749160B1